The Relationship Between the Human Development Index (HDI) and Poverty Rate in North Sumatra in 2023: Spearman Correlation Analysis - Hutapea, Risca Octaviyani; Triyunita, Gizka; Amalia, Sisti Nadia (Holistic Science, 2025)
This study aims to analyze the relationship between the Human Development Index (HDI) and poverty levels in 33 regencies/cities across North Sumatra Province in 2023. The background of this research is rooted in the regional disparities in welfare and the strategic role of human development in poverty alleviation efforts. The data used are secondary data sourced from Statistics Indonesia (BPS), comprising HDI scores and poverty rates. The analytical methods applied include descriptive analysis, the Shapiro-Wilk normality test, and the Spearman rank correlation test, which is appropriate for non-normally distributed data. The findings reveal a significant negative correlation between HDI and poverty with a Spearman correlation coefficient of -0.5936 and a p-value of 0.0003. This indicates that regions with higher HDI tend to have lower poverty rates. The results highlight the importance of improving education quality, healthcare services, and living standards as key strategies in reducing poverty. This study is expected to contribute to the formulation of inclusive regional development policies that prioritize human well-being.